Changes in the Concentration of Chemical Elements in Wastewater in Al-Bayda City After Algal Treatment (Al-Farooq Journal of Sciences, 2026)
This study aims to evaluate the efficiency of algal treatment in reducing chemical pollutants in wastewater from Al-Bayda City. The experimental design was based on a triplicate system over a contact period of eight days under laboratory conditions (photoperiod of 16:8 hours light:dark). Samples were analyzed before and after treatment to determine the concentrations of phosphorus, total dissolved salts, nitrates, and ammonia. Chemical analysis using Atomic Absorption Spectroscopy (AAS) revealed a statistically significant reduction (P < 0.05) in phosphorus (31.5%) and nitrates (48.9%), while no significant change was observed in total salts. Conversely, ammonia concentration increased significantly, which can be attributed to algal biomass decomposition and metabolic by-products. The findings confirm the potential of algae as a sustainable bioremediation tool for nutrient removal, while highlighting the need to develop integrated treatment systems to control ammonia levels
Keywords: Wastewater, Algal Treatment, Phosphorus Removal, Nitrate Reduction,Ammonia Variation, Bioremediation